Hardware in the loop simulation of photovoltaic system with industrial PLC (2019)
"The efficiency in the voltage boost converters becomes increasingly important in low power applications, added to this, there is great difficulty between the design and validation of different configurations or changes in the components that are part of the converters. This paper presents the design and simulation of an MPPT control system based on a voltage boost converter for an array of photovoltaic cells, it is also presented the design and implementation of a monitoring system for the interconnection of 3 voltage boost converters with a programmable logic controller. The tests carried out show a reduction of 33% of the voltage required for the transistor operation, as well as a efficient use of the converters implemented through the PLC incorporation."--Tomado del Formato de Documento de Grado.